2015
DOI: 10.7494/geol.2015.41.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals from waste water using a hybrid membrane process

Abstract: CC-BY 4.0 License requiring that the original work has been properly cited.Soil and water pollution by heavy metals is currently a very important problem in environmental and other sectors. The origin of metals in water may be of either natural character (erosion of rocks and sediments, leaching of mineral resources) or anthropogenic character (mining and extraction of metals, industry, agriculture, etc.) (Martins et al. 2010). Many heavy metals, such as Pb, Cd, Cu, Zn, etc., are the most polluting factors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was also reported that the passage of ions through nanotubes was related to the diameter of the BN nanotubes. Sabo et al (2015) described a hybrid membrane processes for the removal of metal ions from water. This method includes two processes: adsorption of metal ions on the natural zeolite and microfiltration of zeolite suspension through ceramic membrane.…”
Section: Ceramic Membrane/materials For Membrane Adsorptionmentioning
confidence: 99%
“…It was also reported that the passage of ions through nanotubes was related to the diameter of the BN nanotubes. Sabo et al (2015) described a hybrid membrane processes for the removal of metal ions from water. This method includes two processes: adsorption of metal ions on the natural zeolite and microfiltration of zeolite suspension through ceramic membrane.…”
Section: Ceramic Membrane/materials For Membrane Adsorptionmentioning
confidence: 99%